2011
DOI: 10.1152/ajpregu.00642.2010
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-rest cycles do not alter local and whole body heat loss responses

Abstract: Previous studies have suggested that greater core temperatures during intermittent exercise (Ex) are due to attenuated sweating [upper back sweat rate (SR)] and skin blood flow (SkBF) responses. We evaluated the hypothesis that heat loss is not altered during exercise-rest cycles (ER). Ten male participants randomly performed four 120-min trials: 1) 60-min Ex and 60-min recovery (60ER); 2) 3 ϫ 20-min Ex separated by 20-min recoveries (20ER); 3) 6 ϫ 10-min Ex separated by 10-min recoveries (10ER), or 4) 12 ϫ 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Mean skin temperature (Tsk) was calculated using a modified version of the formula reported by Nadel et al The SR on the forehead (center of the forehead), chest (below the clavicle), forearm (center of the left ventral forearm), and palm (between the left thumb and wrist) were measured continuously using the ventilated-capsule method. Because it has been reported that the SR caused by isolated muscle mechanoreflex activation is small (below 0.1 mg·cm 2 ·min Ϫ1 ) (23), we used smaller sweat capsules (1.54 cm 2 ) and greater dry nitrogen gas flow (500 ml/min) to the capsules (nitrogen gas rate/capsule area ϭ 324 ml/cm 2 ) than previous studies [147-248 ml/cm 2 (13,25,28,39,45)] to detect small changes in the response. The capsules were carefully attached to the skin with glue.…”
Section: Methodsmentioning
confidence: 99%
“…Mean skin temperature (Tsk) was calculated using a modified version of the formula reported by Nadel et al The SR on the forehead (center of the forehead), chest (below the clavicle), forearm (center of the left ventral forearm), and palm (between the left thumb and wrist) were measured continuously using the ventilated-capsule method. Because it has been reported that the SR caused by isolated muscle mechanoreflex activation is small (below 0.1 mg·cm 2 ·min Ϫ1 ) (23), we used smaller sweat capsules (1.54 cm 2 ) and greater dry nitrogen gas flow (500 ml/min) to the capsules (nitrogen gas rate/capsule area ϭ 324 ml/cm 2 ) than previous studies [147-248 ml/cm 2 (13,25,28,39,45)] to detect small changes in the response. The capsules were carefully attached to the skin with glue.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the time taken to balance the differential rates of whole body heat production and heat loss (i.e., thermal inertia) is reduced when core temperature is elevated and the body is already warm (7,21,22). The greater rate of whole body heat loss with repeated exercise, known as the priming effect (7), has been shown to reduce the amount of heat gained during the subsequent exercise periods (21).…”
Section: Whole Body Heat Loss With Successive Exercise Periodsmentioning
confidence: 99%
“…There is also a lack of information on the underlying pathways governing the control of sweating following exercise and during a subsequent exercise bout. Studies show that there is a more rapid increase in sweating during subsequent exercise compared to the first bout, and this has been termed the priming effect (Gagnon & Kenny, ). However, this is not paralleled by a more pronounced rate of heat dissipation in recovery.…”
Section: Introductionmentioning
confidence: 99%